Aportación al catálogo pteridoflorístico de la provincia de Málaga - Nieto, J. M.; Pérez Latorre, A. V.; Cabezudo, Baltasar; Boyero, J. R.; Escámez, A. M.; Salvo, A. E. (Acta Botanica Malacitana, 1988)
.